Addressing religious practices in Sub-Saharan Africa. Insights from a longitudinal study in rural Mali - (:unkn) unknown (My University, 2020)
In censuses and demographic surveys, religion is recorded as a variable of state, assuming that individuals’ religious affiliation is unique and definitive. However, in sub-Saharan Africa, pluralism are commonplace. In this paper, we discuss the relevance and feasibility of a statistical approach to religious practices, taking into consideration their complexity and variability over an individual’s lifetime. We use longitudinal data collected since 25 years in the south-east of Mali, among a population where traditional and Christian religions coexist. We can compare the results of a classic cross-sectional approach with those obtained via a longitudinal approach that takes into consideration individuals’ religious trajectories. Plurality and variability in religious practices are confirmed. Most individuals, at some point in their lives, become affiliated with different religions. Mobility and reversibility in religious affiliation are common. The relevance of cross-sectional data on religious affiliation for demographic analysis is questionable.
Keywords: African Research